Estructura hidrográfica de la Bahía de Bluefields, Nicaragua - Brenes, C. L. (Universidad de Costa Rica, 2009)
In March and October of 2000, under the DIPAL II project (Proyecto para el Desarrollo Integral de la Pesca Artesanal en la Región Autónoma del Atlántico Sur), two hydrographic surveys were carried out in the Bay of Bluefields to study their hydrography during the dry and rainy seasons. Water temperature, salinity and turbidity were determined both at the surface and the bottom of the bay. The results obtained are consistent with previous studies carried out in this area. In March, water temperature and salinity were lower and higher, respectively, than in October. Water turbidity increased with increased fresh water input as a result of a greater movement of suspended sediments and organic matter into the water body. Saline wedges were observed in deep strata during the two months of sampling in the adjacent areas to the bars of The Bluff and Hone Sound. In the first case the wedge extended to the northwest up to the area of Bluefields, while in the second case it extended to the west reaching the western coast of the bay. The vertical gradient of salinity was stronger in October, when the superficial flow of fresh water in the whole bay was more intense. A circulation pattern related to the salinity field was recognised: fresh water introduced by the Caño Negro and Escondido rivers moves along the western coast of the bay, while sea water enters the bay towards the northwest, throughout the whole water column, at the bars of The Bluff and Hone Sound. Fresh water introduced by the River Torsuani moves along the eastern coast towards the open sea at the southern end of the bay.